Oh Mama Boutique / Audrey Annabel Akchimbi ... [et al.] - Akchimbi, Audrey Annabel; Masahor, Nur Afifah Arifah; Yusof Anthony, Amira Farzana; Chek Usup, Nurul Farhana; Wan Mohammed, Sharifah Zahidah (2011)
As a representative of our company; OH MAMA company, I would like to submit our business plan for your to be justify and further action if needed. We are very thankful for the inspiration, recommendation and commitment that have been given by you with the aim ofrealizing this business plan and eventually will anchored us toward aims and goals of the delegated task given until we in the end accomplishing this project in time. Our group’s idea and thoughts towards ETR300 (Introduction to Entrepreneurship) had given us the experience and understanding on the primary goals of starting the business.